Vegan diet: nutritional components, implementation, and effects on adults’ health - Łuszczki, Edyta; Boakye, Faustina; Zielińska, Magdalena; Dereń, Katarzyna; Bartosiewicz, Anna; Oleksy, Łukasz; Stolarczyk, Artur (Frontiers in Nutrition, 2023)
Vegan diet has emerged as a popular dietary choice for people worldwide in recent times, due to concerns such as health issues, animal rights and welfare, and the sustainability of the environment. The purpose of this literature review was to explain how a vegan diet may affect the health of adults and to point out beneficial components found in it as well as any difficulties associated with its implementation. Evidence supports that a vegan diet can reduce the risk of chronic diseases, such as type 2 diabetes, hypertension, and certain types of cancer. A well-planned vegan diet must include adequate calories and nutrients, as well as the necessary supplements, such as vitamin B12, vitamin D and EPA/DHA. Given the current growing interest in plant-based diets among the general population, it is crucial to understand both the barriers, risks, and benefits of the vegan diet among physicians, policy makers, and the general population.